Establishing System Quality In Accredited Biomedical Calibration Laboratory - Abdul Latiff, Roziah (2016)
Medical equipment requires confirmation whether they comply with the specifications and safety regulations before they can be used in healthcare facilities. Politeknik Sultan Salahuddin Abdul Aziz Shah (PSA) has set up the biomedical equipment analyzer calibration laboratory starting from October, 2010. These stations are capable to test and calibrate medical device analyzers such as patient simulator, safety analyzer, infusion pump etc. PSA plans to apply ISO/IEC 17025 certification, specifically for laboratory accreditation for the calibration laboratory to ensure and establish its reliability and commitments towards providing quality services. The purposes of this study are to discover the perceived service quality of Biomedical Calibration Laboratory, to analyze the SERVQUAL dimensions in the context of setting-up accredited Biomedical Calibration Laboratory and to evaluate the relationship between the SERVQUAL factors towards the perceived service quality of Biomedical Calibration Laboratory. The methodology used in this research are both quantitative and qualitative method. The five SERVQUAL dimensions: tangible, reliability, responsiveness, assurance and empathy are being used in contributing perceived service quality of Biomedical Calibration Laboratory. The dimensions in this study are used as a guidelines in the quality manual to establish quality service of accredited Biomedical Calibration Laboratory in Malaysia, based on the experience gained after going through the whole systems, the proposed process also can be used by other health care industries.